Laparoscopy Assisted Transjejunal ERCP for Treatment of Pancreaticopleural Fistula - Saleem, Atif; Sawyer, Mark D; Baron, Todd H (JOP. Journal of the Pancreas, 2016)
Context Pancreaticopleural fistula is a rare complication estimated to occur in 0.5% of the patients with pancreatitis and even extremely rare in surgically altered anatomy (e.g. Roux-en-Y anastomosis) patients. The conventional ERCP is difficult to treat pancreaticopleural fistula in a patient with complex upper GI anatomy because of long anatomical route. Case report We represent a case of a 47-year-old female with remote subtotal gastrectomy with Roux-en-Y gastrojejunostomy admitted with recurrent left pleural effusion due to pancreaticopleural fistula. After failed ERCP through the anatomical route, pancreaticopleural fistula was treated successfully with laparoscopy-assisted transjejunal ERCP. Conclusion Laparoscopy-assisted ERCP is a useful modality in patients with surgically altered anatomy. Image: Radiographic image showing endoscope in position passed retrograde.